Waxy Chlamydomonas reinhardtii: monocellular algal mutants defective in amylose biosynthesis and granule-bound starch synthase activity accumulate a structurally modified amylopectin. - Delrue, B (1992)
Amylose-defective mutants were selected after UV mutagenesis of Chlamydomonas reinhardtii cells. Two recessive nuclear alleles of the ST-2 gene led to the disappearance not only of amylose but also of a fraction of the amylopectin. Granule-bound starch synthase activities were markedly reduced in strains carrying either st-2-1 or st-2-2, as is the case for amylose-deficient (waxy) endosperm mutants of higher plants. The main 76-kDa protein associated with the starch granule was either missing or greatly diminished in both mutants, while st-2-1-carrying strains displayed a novel 56-kDa major protein. Methylation and nuclear magnetic resonance analysis of wild-type algal storage polysaccharide revealed a structure identical to that of higher-plant starch, while amylose-defective mutants retained a modified amylopectin fraction. We thus propose that the waxy gene product conditions not only the synthesis of amylose from endosperm storage tissue in higher-plant amyloplasts but also that of amylose and a fraction of amylopectin in all starch-accumulating plastids. The nature of the ST-2 (waxy) gene product with respect to the granule-bound starch synthase activities is discussed.